KOMPETENSI KEPALA SEKOLAH DALAM MEMBINA PROFESIONAL GURU IPA - Intan Hastiningrum (Manajer Pendididikan, 2016)
The purpose of this research is to describe the competence of principal in coaching profesional of science teachers at Public Junior High School No. 1 Ketahun of North Bengkulu. The method used in this research is a qualitative descriptive study. Data collection techniques through interviews, observations, and document study. The data analysis are data reduction, data display, and conclusion drawing/ verification. The result of this research show that the competence of principal which consist of personality competency, managerial competency, entrepreneurship competency, supervision competency, and social competency has implemented by the principal in coaching profesional of science teachers.Keywords: principal, competence, science teachers